Pengembangan ChemOnPhone dalam Model Pembelajaran Berbasis Masalah untuk Meningkatkan Motivasi Belajar Peserta Didik - Anugrah, Joulman Cipta Alief; Sudding, Sudding; Sulfikar, Sulfikar (Chemistry Education Review (CER), 2021)
This study aims to increase the learning motivation of students in studying the subject matter of chemical equilibrium. Therefore, we developed learning application based smartphone in a problem-based learning model that called ChemOnPhone which is valid, practical and effective to use. To achieve this aim, we followed the Hannafin and Peck's model development phases: analysis, design, development and implementation. The ChemOnPhone we built had been through validation processes by an educational media and a subject content experts. We then revised the app accordingly by considering these expert reviews until the app considered as valid.  To evaluate the practicality and the effectiveness of the app, we then tried it out to Year XI Science students of SMAN 2 Sidrap. The results of media validation and trial showed that: (1) the media was very valid (marked 3.93 out of 4), (2) the content was valid (marked 3.01 out of 4). ChemOnPhone was also considered practical and effective based on (1) The implementation was graded as effective (M = 1.85, 1.5 ≤ M ≤ 2.0), (2) The approval rate was 97.2% and 86.4% by teachers and students, accordingly. ChemOnPhone has met the effective criteria as (1) students learning motivation improved from 60.9% out of 84.4%, (2) students learning activity was averagely 87.5%, which met the active criterion, and (3) the average learning results achieved was 88.4% out of 100%, which pass the effective criteria of ≥ 80%. Overall, ChemOnPhone was valid, practical and effective to use in learning the chemical equilibrium subject.